(untitled) (Agroindustrial Science, 2026)
This study evaluated the antifungal activity of essential oils from Cinnamomum verum, Tagetes lucida and Syzygium aromaticum against Fusarium oxysporum isolated from avocado (Persea americana Mill.). The oils were tested at concentrations of 1.0%, 0.5%, 0.1%, 0.05% and 0.01% using the agar diffusion method, with four replicates per treatment. Mycelial growth was measured daily for seven days, and the inhibition percentage and area under the growth curve were calculated. Significant differences (p ≤ 0.05) were observed among treatments, with C. verum being the most effective, achieving over 70% inhibition at 1.0% concentration. T. lucida and S. aromaticum showed moderate antifungal effects, with mycelial growth reductions up to 60%. Phytotoxicity assays on P. americana calli revealed no visible damage, except for slight yellowing with C. verum at 1.0%. These findings highlight the potential of essential oils as sustainable biotechnological alternatives for the management of F. oxysporum in avocado cultivation